Dukungan Keluarga pada Kemandirian Lansia dalam Melakukan Aktivitas Sehari-Hari: Studi Kualitatif - Mulyadi Mulyadi; Yossy Utario (Poltekkes Kemenkes Bengkulu, 2022)
The elderly experience various health problems that can decrease independence in carrying out daily activities. Optimal family support can encourage increased independence of the elderly. This study aims to determine the experience of families providing support to the elderly in carrying out daily activities. The research method used in this research is a qualitative study with a phenomenological approach. Sampling using purposive sampling. Participants in this study were 10 elderly family members. The criteria for participants are family members or people who are closest to the elderly at home, willing to be participants and willing to tell their experiences, and the age of the elderly is in the range (of 66-75 years). The data was collected in recordings and field notes and analyzed using the Collaizi technique. The results of this study obtained four themes, namely 1) Forms of emotional expression, 2) Health care for the elderly, 3) Helping to meet the needs of the elderly, and 4) Family assessment for the elderly. Family support for the elderly appears in various forms of different responses. It is recommended for families to increase support for the elderly to maintain or maintain their independence of the elderly as much as possible.